Hedgers Competition in Financial Market - Jiao, Letian; Zhang, Tianyu; Chen, Haitao (International Journal of Advanced Engineering, Management and Science, 2021)
We analyze a two-period model with two kinds of hedgers who have different kinds of non-tradable risky asset to hedge. For holding the asset whose payoff is related to a tradable risky asset, they can derive some different private information about this tradable risky asset. Both hedgers have demand to buy risky asset for the purpose of speculating and hedging. In date 1, they get the information about their non-tradable asset position, private signal of tradable risky asset’ payoff and decide how much tradable risky asset they want to hold. They can estimate each other’s private information through equilibrium price. We also measure the information passing effect of price.